KUALITAS PELAYANAN KESEHATAN PASIEN BPJS DI RUMAH SAKIT ISLAM SITTI MARYAM MANADO - BANDU, SULASTRI; RUMAPEA, PATAR; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2018)
Health care is one of the fundamental rights of societies that are organized by the mandatory Government arranged. One important element in the system of hospital is labour, organization and quality of medical personnel and nurses in the hospital, because it will affect the quality of the management and service. Therefore the hospital as a health care provider must provide satisfying service towards patients Social Insurance Administration Organization (BPJS). Because the hospital is an organization that sells services, then a quality service is one of the demands that must be met. Hence the need for an action that is truly concerned with the public interest in terms of providing services that are really good to society. The purpose of this research is to know the patient's medical service quality in hospital BPJS Islam of Sitti Maryam Manado. This study uses qualitative methods. Informants in this study amounted to seven people. Data collection techniques used are interviews, observation and documentation. Measurement using the theory of Parasuraman with five dimensions of service quality that is reliability, empathy, intangibles, responsiveness, assurance. The results of this study stated that by using five dimensions of service quality measurement of the health of the patient in hospital BPJS Islam of Sitti Maryam Manado votes is enough. More suggestions improve existing facilities and infrastructure at the Islamic Hospital of Sitti Maryam Manado in order to support existing services. Hospital employees should mutually enhance the sense of the importance of hospitality towards the patient or patient's family in the service of process in order for the patient or the patient's family gave a good response against an employee of the hospital. Keywords: Quality Of Service, Patient BPJS